Posterior reversible encephalopathy syndrome in dengue: a rare manifestation - Kaur, Manjot; Singh, Pushpinder; Bansal, Anshul (International Journal of Research in Medical Sciences, 2022)
Dengue is an important arthropod born disease with its cases spiking every 2-3 years and spectrum of disease ranging from mild febrile illness to severe illness with multiple systemic complications including rare neurological manifestation. We hereby presented a case report of rare presentation of posterior reversible encephalopathy syndrome (PRES) in an eight year old child suffering from dengue.